2013
DOI: 10.1063/1.4811759
|View full text |Cite
|
Sign up to set email alerts
|

Development of high quantum efficiency GaAs/GaInP double heterostructures for laser cooling

Abstract: We report on the growth and characterization of high external quantum efficiency (EQE) GaAs/ GaInP double heterostructures. By properly treating the GaAs/GaInP interface, we are able to produce structures measuring a record EQE of 99.5% 6 0.1% in GaAs. This efficiency exceeds the requirement for achieving laser cooling in GaAs. However, net cooling has not yet been realized due to residual below gap background absorption. V

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…Despite the presently lower EQE, it is typically expected that the electrically injected GaAs system provides the most suitable candidate for EL cooling for a number of reasons. These include (i) the substantially larger reported internal quantum efficiencies (IQE), exceeding 99.5%, 1,18 which is of key importance especially for devices where photons will not be extracted in air; (ii) the mature fabrication technology; 4 and (iii) the potentially higher cooling rates due to the availability of lattice matched materials, allowing optically thick emitter regions and the larger optical density of states following from the larger refractive index. 2 To study EL cooling and the related photon and energy transport effects in GaAs based light emitters in the high power regime in more detail, we recently introduced the double diode structure (DDS) illustrated in Fig.…”
mentioning
confidence: 99%
“…Despite the presently lower EQE, it is typically expected that the electrically injected GaAs system provides the most suitable candidate for EL cooling for a number of reasons. These include (i) the substantially larger reported internal quantum efficiencies (IQE), exceeding 99.5%, 1,18 which is of key importance especially for devices where photons will not be extracted in air; (ii) the mature fabrication technology; 4 and (iii) the potentially higher cooling rates due to the availability of lattice matched materials, allowing optically thick emitter regions and the larger optical density of states following from the larger refractive index. 2 To study EL cooling and the related photon and energy transport effects in GaAs based light emitters in the high power regime in more detail, we recently introduced the double diode structure (DDS) illustrated in Fig.…”
mentioning
confidence: 99%
“…1. Hence, the DDS arrangement allows direct observation of the lower limit of energy transfer between LED and PD, quantitatively expressed with the coupling quantum efficiency (CQE) defined as the ratio CQE = I 2 ∕I 1 , while circumventing the light extraction problems encountered in high-efficiency light emitter setups (Broell et al 2014;Hurni et al 2015;Gauck et al 1997;Bender et al 2013). The CQE is a central experimentally accessible figure of merit in the DDS context, as ELC can only be observed if the condition PCE = CQE � ∕U > 1 for the power conversion efficiency (PCE) is met.…”
Section: The Double Diode Structurementioning
confidence: 99%
“…[32][33][34][35] One of the most intensively studied semiconductor devices for optical refrigeration are GaAs based quantum wells, whose EQE can be as high as 99.5%. 36,37 However, due to strong parasitic absorption, net cooling has not been achieved in III-V quantum wells. In 2013, Zhang et al reported the first laser cooling of 40 K in in CdS nanowires, which have strong coupling of exitons and longitudinal optical phonons (LOP), high EQEs, and weak parasitic absorption.…”
Section: Optical Refrigerationmentioning
confidence: 99%